The Implementation of the 2013 Curriculum: Concept, Application and Quantitative, Qualitative and R&D Approaches - Dahoklory, Franklin Stevan; Saputri, Dwi Yuniasih; Arisandi, Duddy; Tuamely, Julita; Sappaile, Baso Intang (International Journal of Educational Research Excellence (IJERE), 2024)
Curriculum alterations have become a common occurrence, coincident with advances in technology and informational resources. This is designed to maintain alignment with the current educational landscape and to ensure relevance to contemporary times. Research is a scientific process that is formal and intensive. This is because it refers to established rules, cycles, and ways of representation that are necessary to obtain results that are recognized and beneficial to human life. The methodology employed in this research study was a systematic review of the literature. This approach was utilized to describe and elucidate the fundamental tenets of qualitative, quantitative research, as well as research and development initiatives associated with the implementation of the 2013 Curriculum. This result of the study is the concepts of qualitative, quantitative, and research & development research—along with their respective characteristics, types, and applications—offer significant benefits in the realm of education, particularly in the context of curriculum development. These research methodologies, which are commonly utilized in educational settings, align with the 2013 curriculum guidelines, facilitating studies or research related to education, thereby enabling more effective and impactful outcomes.